PENINGKATAN KEMAMPUAN MENGAJAR GURU MELALUI KEGIATAN SUPERVISI DI SMP NEGERI 1 KAMPAR TIMUR KABUPATEN KAMPAR - Mulhadi Mulhadi (JURNAL PAJAR (Pendidikan dan Pengajaran), 2018)
This study aims to determine whether the supervision activities to improve teachers' teaching skills in SMPNegeri 1 Kampar Timur, Kampar. Based on background description, problem identification and problemrestriction, the focus of this research is related to supervision activities to improve teachers' teaching abilities inSMP Negeri 1 Kampar Timur, Kampar. The School Action Research is conducted only at SMP Negeri 1 KamparTimur Kampar District. In one supervision of the researcher himself. The type of this research is School ActionResearch (PTS) located in SMP Negeri 1 Kampar Timur, Kampar, which is aimed at teachers. The main reasonis from the results of observation and information from teachers, that pedagogic competence of teachers is stillclassified as less. The sample in this study is all teachers in SMP Negeri 1 Kampar Timur, Kampar amounted to55 people. From the description of data processing and discussion, it can be concluded that the pedagogiccompetence of teachers obtained in the first cycle of 60% with good category and on the second cycle increasedto 80% with good category. This means that supervision activities can improve teachers' teaching skills in SMPNegeri 1 Kampar Timur, Kampar is said to succeed.